Distribution and status of the Greater Sandhill Crane in Wisconsin - Gluesing, Ernest A. (University of Wisconsin-Stevens Point, 1974)
The greater sandhill crane (Grus canadensis tabida) was studied from September, 1972, through November, 1973. Important nesting habitats are river marshes, lake marshes, flooded meadows, cattail marshes, sedge marshes, cranberry reservoirs, and bogs. The mean size of 143 marshes where one or more pairs of sandhill cranes were located was 339 acres. Approximately 850 sandhill cranes were present in Wisconsin during the summer of 1973. Of the 250 known pairs, nests were located for 40 pairs and 66 pairs were known to have produced 87 young. An estimated 55 additional pairs were not observed and an estimated 152 cranes were present as non-breeders. Thirty-three nests had a mean clutch size of 1.788 and 55 percent of all known nests were on land in private ownership. The densities of cranes in Wisconsin were low in relation to other North American populations indicating that the number of cranes in Wisconsin should continue to increase if their habitat is preserved. White collars were placed on 29 cranes and measurements of 36 captured cranes indicated that none could be definitely classified as belonging to the rowani subspecies.